Organizing Women in the Spaces between Home, Work and Community - Yates, Charlotte (Relations industrielles / Industrial Relations, 2011)
Since women began mobilizing more than 40 years ago to transform the labour movement, unions have made significant changes to increase women’s participation, leadership and interest representation. Yet, there are limitations to this progress. Unionized women are concentrated in the public sector amongst full-time employees. Moreover, women’s interests have tended to be added onto existing union agenda; women are therefore encouraged to adjust to existing union structures and practices rather than unions undertaking transformational organizational change. Unions tend to socially construct the collective interests and identities of women workers in gender-neutral ways that end up limiting union capacities to make bigger organizing breakthroughs amongst women. The article develops an argument that women’s relationship to work is distinct from men’s. Women are more likely to experience a blurring of the boundaries between work, home and community, which leads many women workers to be less responsive to union appeals that focus strictly on the job and workplace. These ideas are explored using a case study of a province-wide organizing drive amongst child care providers by the B.C. Government Employees Union (BCGEU). The BCGEU used methods of community unionism to build a sense of collective identity and capacity for collective action amongst a diverse group of child care providers, including those who work in child care centres, in-home providers and migrant domestic workers. The union built its campaign around shared relationships of caring and love, and by rejecting the devaluation of child care as unskilled, women’s work. The article concludes with an evaluation of whether this approach to organizing women opens new possibilities for reaching out to non-union women.